ANALYSIS OF PROFESSIONALISM, COMPETENCY AND INDEPENDENCE ON AUDIT QUALITY IN PUBLIC ACCOUNTING FIRM IN PALEMBANG CITY. - Adin, Adindia; Nurmala; Panca Satria Putra (Jurnal Ecoment Global, 2024)
Objective: This is to determine the effect of professionalism, competency and independence analysis on audit quality at Public Accounting Firms in Palembang. ”   Design/method/approach: " This research uses quantitative methodology and utilizes SPSS 26 as a measuring tool. The population of this research is five Public Accounting Firms in Palembang. Because of the quantitative approach used in the sampling methodology, the sample used was 33 respondents.   Results: This research shows that with a significance value of 0.015 <0.05, H1 is rejected due to incomplete professionalism. With a significance value of 0.001 <0.05, competency has a fairly large influence on audit quality; so, H2 is approved. Additionally, independence has little impact on audit quality; when this effect is statistically significant 0.789 > 0.05, H3 is rejected. If a simultaneous significance value of 0.000 is found, which means less than 0.05, then H4 is approved. Audit quality is significantly influenced by professionalism, competence and independence simultaneously.  Practical/policy implications: It is hoped that the findings of this study will guide future investigations. Keywords: Professionalism, Competence and Independence on Audit Quality.